Documento de Idoneidad Técnica -TAPIFLEX "CONFORT". -C.D.U.: 69.025.356 S.F.B. (43) Tn - Convalidación n. 2 Agrément del C. S. T. B. n.° 1933, Fecha: 27-111-1965 - Revestimiento de suelos - Nadal, J. (Informes de la Construcción, 1965)
No disponible